The Personalities of Significant Others in Association with Regular Drinking in Adolescence - Georgi Sarov (Journal of Biomedical & Clinical Research, 2016)
It is well known that some psychological features of adolescents are positively associated with alcohol drinking but less attention is paid to the psychological features of their significant others. The aim of the study was to describe a common psychological profile of significant others to regularly alcohol drinking adolescents. A survey was conducted using an original questionnaire, which classifying alcohol drinking as regular, social (incidental) and abstinence. Of 903 students (aged 15-19), 169 identified themselves as regular drinkers (RDA) and 279 - as abstainers (NDA). The significant others of these two groups were compared statistically in terms of a wide range of psychological features. It was found that RDAs were significantly more likely to have: fathers (OR=1.94; 95% Cl 1.04-3.62) and friends (OR=l .55; 95% Cl 1.02-2.36) that tended to avoid obligations in favor of pleasure; extravert friends (OR=1.55; 95% Cl 1.06-2.28) and lovers (OR=1.72; 95% Cl 1.14-2.59); impulsive lovers (OR=l .76; 95% Cl 2.86- 1.08), and obeying (OR=l .95; 95% Cl 1.01-3.80) friends; conventional fathers (OR=2.17; 95% Cl 1.27-3.72) and less likely to have independent mothers (OR=0.57; 95% Cl 0.32-0.99) and hardworking friends (OR=0.58; 0.35- 0.95). It seems that significant others of RDAs are less likely to exhibit models of rational reactions in everyday life that prevent adolescents from developing rational personality, thus making it possible to increase the probability of regular drinking in adolescence.